Sexual Orientation, Gender Identity, and Substance Use: Using the Social Structure-Social Learning Model to Explore Drug Use in the LGBTQ+ Community - Stogner, John (Crime & delinquency, 2024)
Members of the lesbian, gay, bisexual, transgender, queer, and other gender and sexual minority (LGBTQ+) community are disproportionately affected by illicit substance use, yet sexual orientation and gender identity are largely omitted from criminology frameworks. LGBTQ+ identity is incorporated into Akers? Social Structure-Social Learning (SSSL) model to suggest that existing disparate substance use patterns may be attributed to variation in substance-related definitions, peer models, and reinforcement. Data from 2,349 young adults were used to estimate structural equations models. LGBTQ+ respondents reported greater substance use than peers. Consistent with theoretical expectations, this relationship was fully mediated by social learning constructs. This study justifies incorporating sexual orientation and gender identity into the SSSL model and suggests peer-based substance use interventions are particularly influential within the LGBTQ+ community.